The romantics : a novel - Mishra, Pankaj (New York : Random House, 2000)
The young Brahman Samar has come to the holy city of Benares to complete his education and take the civil service exam that will determine his future. But in this city redolent of timeworn customs, where pilgrims bathe in the sacred Ganges and breathe in smoke from burning ghats along the shore, Samar is offered entirely different perspectives on his country. Miss West and her circle, indifferent to the reality around them, represent those drawn to India as a respite from the material world. And Rajesh, a sometimes violent, sometimes mystical leader of student malcontents, presents a more jaundiced view. More than merely illustrating the clash of cultures, Mishra presents the universal truth that our desire for the other is our most painful joy.
Keywords: English fiction -- Indic authors; College students -- Fiction; East and West -- Fiction; Young men -- Fiction; Varanasi (India) -- Fiction; Indic fiction